2020
DOI: 10.1186/s12913-020-05537-3
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of comprehensive medication management for chronic diseases in primary care clinics, a Texas delivery system reform incentive payment program

Abstract: Background: The Institute of Medicine reported that more than 1.5 million preventable adverse drug events occur annually in the United States. Comprehensive Medication Management (CMM) is the medication review process to improve clinical outcomes, enhance patient adherence, reduce drug therapy problems and reduce health care costs. University of Texas (UT) Physicians implemented a CMM program in several community-based clinics. We evaluated the effectiveness of CMM to reduce drug therapy problems and achieve m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 7 publications
0
41
1
Order By: Relevance
“…A few limitations should be noted in our study. It is not clear why our MTP acceptance rates were lower than in other studies, which found typical acceptance rates that range from 37% to 59.6% 13–16 . For example, it is unclear whether providers saw the recommendations and disagreed with the assessment of the pharmacist or if they simply failed to notice the recommendations.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…A few limitations should be noted in our study. It is not clear why our MTP acceptance rates were lower than in other studies, which found typical acceptance rates that range from 37% to 59.6% 13–16 . For example, it is unclear whether providers saw the recommendations and disagreed with the assessment of the pharmacist or if they simply failed to notice the recommendations.…”
Section: Discussioncontrasting
confidence: 69%
“…It is not clear why our MTP acceptance rates were lower than in other studies, which found typical acceptance rates that range from 37% to 59.6%. [13][14][15][16] For example, it is unclear whether providers saw the recommendations and disagreed with the assessment of the pharmacist or if they simply failed to notice the recommendations. We also did not examine whether the rate of acceptance or the types of MTPs identified chan- Due to an oversight however, an MTP for the need for monitoring for effectiveness was not included on the standardized documentation form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After preliminary screening, 250 articles needed to be further screened. Twenty-seven articles ( Patel et al, 2005 ; Gisev et al, 2009 ; Gomez et al, 2009 ; Hooper et al, 2009 ; Zhao, 2012 ; Roth et al, 2013 ; Lenander et al, 2014 ; Nadir et al, 2014 ; Tan et al, 2014 ; Mendonca et al, 2016 ; Okumura et al, 2016 ; Rodis et al, 2017 ; Schwartz et al, 2017 ; Benson et al, 2018 ; Vande Griend et al, 2018 ; Yang et al, 2018 ; Hazen et al, 2019 ; Khera et al, 2019 ; Neves et al, 2019 ; Santos et al, 2019 ; Zhang et al, 2020a ; Zhang et al, 2020b ; Chung et al, 2020 ; Gerard et al, 2020 ; Puspitasari et al, 2020 ; Samir Abdin et al, 2020 ; Troncoso-Marino et al, 2020 ) were finally included (there were only 26 studies because one of the studies was reported in two articles) ( Zhang et al, 2020a ; Zhang et al, 2020b ). The process of study selection is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, 61.54% ( n = 16) were from developed countries, including six from America ( Patel et al, 2005 ; Roth et al, 2013 ; Rodis et al, 2017 ; Schwartz et al, 2017 ; Vande Griend et al, 2018 ; Chung et al, 2020 ), three from Canada ( Khera et al, 2019 ; Gerard et al, 2020 ; Samir Abdin et al, 2020 ), three from Australia ( Gisev et al, 2009 ; Tan et al, 2014 ; Benson et al, 2018 ), two from Spain ( Gomez et al, 2009 ; Troncoso-Marino et al, 2020 ), one from the Netherlands ( Hazen et al, 2019 ), and one from Sweden ( Lenander et al, 2014 ); 38.46% ( n = 10) were from developing countries, including four from Brazil ( Mendonca et al, 2016 ; Okumura et al, 2016 ; Neves et al, 2019 ; Santos et al, 2019 ), three from China ( Zhao, 2012 ; Yang et al, 2018 ; Zhang et al, 2020a ; Zhang et al, 2020b ), two from Qatar ( Hooper et al, 2009 ; Nadir et al, 2014 ), and one from Indonesia ( Puspitasari et al, 2020 ). According to the types of study design reported by the authors, there were six prospective studies ( Hooper et al, 2009 ; Roth et al, 2013 ; Rodis et al, 2017 ; Benson et al, 2018 ; Yang et al, 2018 ; Zhang et al, 2020a ; Zhang et al, 2020b ), five cross-sectional studies ( Zhao, 2012 ; Nadir et al, 2014 ; Okumura et al, 2016 ; Hazen et al, 2019 ; Troncoso-Marino et al, 2020 ), four retrospective studies ( Mendonca et al, 2016 ; Vande Griend et al, 2018 ; Chung et al, 2020 ; Gerard et al, 2020 ), five before-and-after controlled or longitudinal studies ( Gomez et al, 2009 ; Tan et al, 2014 ; Khera et al, 2019 ; Neves et al, 2019 ; Samir Abdin et al, 2020 ), and one rand...…”
Section: Resultsmentioning
confidence: 99%